The politics of institutionalization, professionalization and quality maintenance: Revisiting the formative years of the academy of pedagogy, 31 1972-1984 - Fentahun Ayele; Tsegaye Berhe (College of education, Bahir Dar University, 2023)
The Academy of Pedagogy was established in 1972 following an agreement signed between the imperial government of Ethiopia and UNDP and UNESCO. During its formative years, the Academy faced enormous challenges. The Academy's institutionalization and professionalization attempts were undermined by the early turbulent years of the Ethiopian Revolution and the subsequent political turmoil and violence. The quality of its training program was also tarnished by the shortage of highly qualified instructors. Through time, however, the Academy managed to overcome the daunting academic and administrative difficulties. This paper, therefore, attempts to outline the evolution of the Academy and investigate the major challenges it faced during the first ten years following its foundation. It also highlights the curriculum revisions undertaken by Bahir Dar Teachers' College in order to ensure quality in its training programs.